Kraft pulping and ECF bleaching of Eucalyptus globulus pretreated by the white-rot fungus Ceriporiopsis subvermispora - doi: 10.4025/actascitechnol.v34i3.12410 - Salazar, Claudio; Mendonça, Regis Teixeira; Baeza, Jaime; Freer, Juanita (Acta Scientiarum. Technology, 2012)
Eucalyptus globulus wood chips were decayed by the lignin-degrading fungus Ceriporiopsis subvermispora as a pretreatment step before kraft pulping. Weight and component losses of wood after the biotreatment were the following: weight (5%), glucans (1.5%), xylans (4.3%), lignin (5.7%) and extractives (57.5%). The residual amount of lignin (expressed by the kappa number) in pulps from biotreated wood chips was lower than that of pulps from the undecayed control. Depending on the delignification degree, kraft biopulps presented similar or up to 4% increase in pulp yield and 20% less hexenuronic acids (HexA) than control pulps. The extended delignification with O2 decreases approximately 50% of the kappa number of the pulps and increases brightness, but had no effect in HexA reduction. The bleaching steps with chlorine dioxide (D0ED1 sequence) decreased the kappa number up to 97%, increased pulp brightness up to 84% ISO and decreased HexA amount up to 91%. The use of C. subvermispora in biopulping of E. globulus generated important benefits during the production of kraft pulps that are reflected in a high pulp yield, low residual lignin content, low HexA amount, high brightness and viscosity of the biopulps as compared with pulps produced from untreated wood chips.